Social determinants of dementia: a scoping review - Walsh, Sebastian; Klee, Matthias; Hui, Esther K.; Saeed, Usman; Waters, Sheena; Kuhn, Isla; Siette, Joyce; Orgeta, Vasiliki; Stafford, Jean; Smith, Laura J.; Tamburin, Stefano; Jensen, Daria E. A.; et al. (Alzheimer's and dementia, 2025)
Dementia risk is influenced by the social conditions in which people live. These social determinants of dementia (SDOD) are potential targets for prevention. We conducted a comprehensive scoping review to identify current evidence on SDOD in two stages: (1) review of systematic reviews on SDOD; and (2) review of primary literature to address identified gaps in the evidence base. Of the 3445 articles screened, 26 reviews and 74 primary studies were included. Evidence from reviews provide clear and consistent patterns for some SDOD (e.g., education, air pollution, socioeconomic status, ethnicity), while evidence for others is still emerging (e.g., housing quality/stability), or lacking entirely (e.g., incarceration). SDOD are important over the life course. Additional evidence is needed for understudied domains and to unravel the complex interactions between determinants, whilst education and air pollution stand out as key targets for public health interventions.Highlights There is clear and consistent evidence for some social determinants of dementia (SDOD) across diverse domains. Evidence for other SDOD (e.g., housing, incarceration) is still emerging or lacking. Evidence for SDOD comes mainly from high-income countries. The complex intercorrelations between SDODs demand a nuanced analytical approach. Standardized measures and longer follow-up to study SDOD are recommended.